Adoption of Improved Cassava Varieties by the Women Farmers in Akinyele Local Government area of Oyo State - O.J., Aluko; H.O, Shaib-Rahim; O.G, Ogunwale (International Journal of Environment, Agriculture and Biotechnology, 2019)
The study investigates adoption of improved Cassava varieties by women in Akinleye Local Government area of Oyo State. 92 respondents were selected using multi stage sampling techniques. Data on sources of input used, adoption of cassava varieties and problem been faced in process of adoption of improved varieties were collected through structured interview schedule. The data was later analyzed using descriptive and inferential analysis. The findings revealed that most ( 29.3% )of the respondents were between age 30 to 40years, 27.3% of the respondents, had no formal education while 43.5% had 5 to 10 years’ experience in cassava farming. The relationship between socio-economic characteristics such age, educational level, farm size, years of farming, labour and adoption level of respondent were determined using chi-square. Inferential statistics shows that there is no significant relationship between age, marital status, secondary occupation and adoption (P>0.05) while education, household size and adoption show significant relationship (P< 0.05). It was observed that most women farmers are late adopters of improved cassava varieties developed by the research institutes in the country. It is recommended that women should liaise with research institute for proper information on current improved cassava varieties in the country.